2012
DOI: 10.4049/jimmunol.1101494
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A Variant of the IL-23R Gene Associated with Inflammatory Bowel Disease Induces Loss of MicroRNA Regulation and Enhanced Protein Production

Abstract: IL-23R gene variants have been identified as risk factors for two major inflammatory bowel diseases (IBDs), Crohn’s disease and ulcerative colitis, but how they contribute to disease is poorly understood. In this study, we show that the rs10889677 variant in the 3′-untranslated region of the IL-23R gene displays enhanced levels of both mRNA and protein production of IL-23R. This can be attributed to a loss of binding capacity for the microRNAs (miRNAs) Let-7e and Let-7f by the variant allele. Indeed, inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 25 publications
0
55
0
1
Order By: Relevance
“…This IL-22 secretion by ILCs is induced upon the production of IL-23 and IL-1b (34,35). Alternatively, a correlation between the susceptibility of inflammatory bowel disease and the IL-23R gene has been demonstrated, showing that a defect in IL-23 signaling can lead to intestinal inflammation (36,37). Alternatively, several inflammatory diseases, including inflammatory bowel disease, are shown to have higher levels of IL-22 in humans (22).…”
Section: Temporary Postnatal Inhibition Of Ra Signaling Affects Silt mentioning
confidence: 99%
“…This IL-22 secretion by ILCs is induced upon the production of IL-23 and IL-1b (34,35). Alternatively, a correlation between the susceptibility of inflammatory bowel disease and the IL-23R gene has been demonstrated, showing that a defect in IL-23 signaling can lead to intestinal inflammation (36,37). Alternatively, several inflammatory diseases, including inflammatory bowel disease, are shown to have higher levels of IL-22 in humans (22).…”
Section: Temporary Postnatal Inhibition Of Ra Signaling Affects Silt mentioning
confidence: 99%
“…The rs10889677 variant in the 3'UTR region of IL-23R gene which led to a loss of binging capacity for let-7e and let-7f displayed increased expression of IL-23R [45] . It means this mutation sustained IL-23 signaling and contributed to chronicity of IBD.…”
Section: Mirnas Regulate Il-23/il-23r Pathwaymentioning
confidence: 99%
“…Recent studies have demonstrated miRNAs to be involved in inflammatory bowel disease (IBD) susceptibility, as polymorphisms in miRNA-binding sites affect the gene expression and thus seem to play a pivotal part in the pathogenesis of this chronic disorder [17,26] . Moreover, it has been found that miRNAs are differentially expressed in ulcerative colitis (UC) and Crohn's disease (CD) [27] , the two main forms of IBD.…”
Section: Introductionmentioning
confidence: 99%